Hybrid model for the generation of tours for tourism and hospitality in a metaverse environment - Alfaro, Luis; Rivera, Claudia; Luna-Urquizo, Jorge; Delgado, Lucy; Castañeda, Elisa (LACCEI, 2025)
Purpose: The emergence of the metaverse presents opportunities and disruptions for users and organizations. This article explores perspectives on the future of digital marketing, proposing a new marketing ecosystem. It discusses strategies that allow organizations to communicate with their customer base in previously unimaginable ways, transforming the concept of marketing into an innovative and groundbreaking field of action. Design/Methodology/Approach: A hybrid system model is proposed for generating immersive virtual tours based on 360° VR videos for hotel environments, their surroundings, and tourist areas. The proposal for a metaverse environment includes designing user interface prototypes that utilize avatars, automating the segmentation of 360° videos using convolutional neural networks, and composing personalized tours based on user profiles through an inference engine employing Case-Based Reasoning (CBR). Findings: Standalone functionality tests within the metaverse for the tour composition component, tailored to user profiles recommended by the CBR inference mechanism, proved successful. Originality/Value: The application of these systems can contribute to reservation intent and brand image improvement, as immersive experiences can trigger effects on affective, attitudinal/behavioral, and cognitive dimensions.